2018
DOI: 10.2147/jpr.s170167
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin regulates dopaminergic neuron firing and theta oscillation in the ventral tegmental area to reverse depression-like behavior in chronic neuropathic pain state

Abstract: PurposeVentral tegmental area (VTA) dopamine system plays an important role in depression and is also involved in pain experience. In this study, we investigated the VTA dopaminergic (DA) neuron firing and local field potential (LFP) in pain-related depression, and we try to explore the underlying relationship between pain and depression.Materials and methodsWe used neuropathic pain model [spare nerve injury (SNI)] to induce pain-related depression. The Dixon up–down method was used to test mechanical hypersen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…We observed that the 50% PWT and sucrose preference percentage were signi cantly decreased, while the immobility time of FST was signi cantly increased due to SNI. Our results reproduced the previous ndings that animals with PNI could display anhedonia and behavioral despair [34,35]. In the current study, PRF-DRG therapy resulted in a dramatic increase in 50% PWT in rats from day 8 to day 42 after SNI, which was consistent with the results reported by Liu et al [36].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that the 50% PWT and sucrose preference percentage were signi cantly decreased, while the immobility time of FST was signi cantly increased due to SNI. Our results reproduced the previous ndings that animals with PNI could display anhedonia and behavioral despair [34,35]. In the current study, PRF-DRG therapy resulted in a dramatic increase in 50% PWT in rats from day 8 to day 42 after SNI, which was consistent with the results reported by Liu et al [36].…”
Section: Discussionsupporting
confidence: 93%
“…It has been demonstrated that partial sciatic nerve ligation induced neuropathic pain significantly decreased the proportion of activated DA neurons in the lateral VTA 63 . However, Fu et al ., found that that spared nerve injury (SNI) can significantly increase the firing rate of VTA DA neurons 64 . These opposite effects may be due to the heterogeneity of DA neurons in VTA and the opposite functions of medial and lateral neurons in VTA 65 .…”
Section: Discussionmentioning
confidence: 99%
“…S1). Some studies have observed depressive symptoms at 2 weeks 77 or 4–6 weeks 64 after spare nerve injury (SNI) surgery in rats. These studies used the same species of animal as our present study, but a different neuropathic pain model.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all these protocol variations, the majority of reported studies could asses a presence of anhedonia from one week (Fang, Zhan, et al, 2019; Goffer et al, 2013; Martinez‐Navarro et al, 2019; Wu et al, 2018; Xu et al, 2017; Zhu et al, 2017) to 10–11 weeks (Fang, Xu, Lin, & Liu, 2019; Fu et al, 2018; Thompson et al, 2018; Wu et al, 2014) after neuropathic pain induction (see also Figures 5 and 6 and Table 1). However, this time window depends on the considered model.…”
Section: Evaluating Anxiety‐like and Depression‐like Behaviours In Anmentioning
confidence: 99%